2010
DOI: 10.1007/s11859-010-0113-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and structure-activity relationships of Schiff bases on Staphylococcus aureus by microcalorimetry

Abstract: The growth of Staphylococcus aureus under the action of six kinds of Schiff bases (A, B, C, D, E, F) was studied by means of microcalorimetry. Growth constant k and inhibition ratio I were calculated. Also, the antibacterial activity, the action characteristics and the structure-activity relationships of the compounds on S. aureus were analyzed. Results indicate that B, F show good antibacterial activity (IC 50 : 293.6 mg • L −1 and 307.8 mg • L −1 ), D, E show moderate antibacterial activity (IC 50 : 966.3 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In disc diffusion method the diameter of the inhibition zone is related to the sensitivity of the isolate and to the diffusion rate of the drug through the agar medium [64]. Diffusion rate of chemical compounds on agar plates may be affected by other factors as: solubility, dipole moment, molecular mass and hydrophobicity [65]; Additionally, chemicals structure might influence their antibacterial activities [66], generally, the electronic nature (electron withdrawing and electron releasing) and position of substituents of the phenyl ring determines the antimicrobial activities [67], studies of structure activity relationship revealed that the presence of electron-withdrawing group Br on the para position of the phenyl rings has a positive effect on the antibacterial activity [68].…”
Section: Antibacterial Activity Evaluationmentioning
confidence: 99%
“…In disc diffusion method the diameter of the inhibition zone is related to the sensitivity of the isolate and to the diffusion rate of the drug through the agar medium [64]. Diffusion rate of chemical compounds on agar plates may be affected by other factors as: solubility, dipole moment, molecular mass and hydrophobicity [65]; Additionally, chemicals structure might influence their antibacterial activities [66], generally, the electronic nature (electron withdrawing and electron releasing) and position of substituents of the phenyl ring determines the antimicrobial activities [67], studies of structure activity relationship revealed that the presence of electron-withdrawing group Br on the para position of the phenyl rings has a positive effect on the antibacterial activity [68].…”
Section: Antibacterial Activity Evaluationmentioning
confidence: 99%
“…They also form basic units in certain dyes [1]. Schiff bases are reported to exhibit antibacterial [2][3][4][5], antifungal [6] and antitumor activity [7]. In addition, the compounds and their metal complexes exhibit interesting photophysical properties [8].…”
Section: Introductionmentioning
confidence: 99%